Antioxidant Activity of Sago (Metroxylon Sagu Rottb) Pith Waste - TUKAYO, BRECHKERTS LIESKE; Wally , Patricia Iveceline Yohana; WANDANSARI, BAIQ DARAQUTHNI (Pharmaceutical Journal of Indonesia, 2024)
Sago pith waste contains flavonoid and tannin compounds. Flavonoids and tannins are well-known phytochemical compounds that act as natural antioxidants that can inhibit free radicals. This study aimed to determine the antioxidant activity of sago (Metroxylon sagu rottb) pith waste extract. Sago pith waste was obtained from Jayapura Regency and extracted by maceration method using 1500 ml of ethanol 70% as a solvent for 5 days. Furthermore, phytochemical screening was carried out on the thick extract. 2,2-Diphenyl-1-picrylhydrazy (DPPH) assay was used to determine antioxidant activity from ethanol extract of sago pith waste with variation in concentration as follows: 100 ppm, 200 ppm, 300 ppm, 400 ppm, and 500 ppm. The study's results found that the secondary metabolite contents of the ethanol extract of sago pith waste were flavonoids, phenolic compounds and tannins. From the antioxidant activity test results, the inhibition percentages of the extracts were 30.98%, 40.66%, 51.15%, 65.90%, and 70%, respectively. The IC50 value of the sago pith waste ethanol extract was found to be 283.11 ppm, which was categorised as weak activity of antioxidants. It can be concluded that sago pulp extract has the potential as a source of natural antioxidants